Retrospective record review on timing of COVID‐19 vaccination and cardiac surgery. Issue 11 (2nd September 2022) - Ho, Jacky Y. K.; Siu, Ivan C. H.; Ng, Karen H. L.; Tam, Matthew; Chow, Simon C. Y.; Lim, Kevin; Kwok, Micky W. T.; Wan, Song; Fujikawa, Takuya; Wong, Randolph H. L.
Abstract: Background: Novel clinical challenges are faced by cardiac surgeons under the coronavirus disease 2019 (COVID‐19) pandemic. Amidst the uncertainties faced due to the socioeconomic and public health impact, there is little evidence surrounding COVID‐19 vaccination in patients undergoing cardiac surgery. Timing of vaccination and postvaccination adverse effects are required parameters to discuss with cardiac surgical patients. Methods: This is a single‐center, retrospective observational study. All patients who underwent adult cardiac surgery at the Prince of Wales Hospital, Hong Kong from January 2021 to December 2021 were included. Postoperative clinical outcomes, COVID‐19 vaccination status, and vaccination‐related adverse effects were collected. Results: A total of 426 patients; 117 (27%) underwent isolated coronary artery bypass grafting, 111 (26%) underwent valvular surgery, and 97 (23%) underwent aortic surgery. Patients received either Sinovac CoronaVac or Pfizer BNT162b2 vaccine. Overall vaccination rate with at least 1 dose was 52% ( n  = 212), 15% ( n  = 63) received the first dose before surgery, 36% ( n  = 149) received the first dose vaccination after surgery. Rate of completion with second and third doses of vaccination were 22% ( n  = 89) and 4.9% ( n  = 20), respectively. The mean timing of first dose of vaccine after surgery was 216 ± 84 days from operation. Three (1.4%) patients recorded vaccination‐related complications. Conclusions: COVID‐19 vaccination is safe in patients who received major cardiac surgery, with low adverse effects recorded and no vaccine‐related mortality observed. A time frame of 3–6 months after cardiac surgery receiving COVID‐19 vaccination is reasonable and could serve as a guidance for future COVID‐19 vaccination booster programs.